Effect of Mother's Level of Knowledge on The Event of Tempera Tantrums in Toddlers - Herlia Agustina; Maryati Sutarno (Science Midwifery, 2022)
The purpose of this study was to determine the relationship between mother's knowledge about the incidence of temper tantrums in toddlers in Jatimakmur Pondok Gede Village, Bekasi City period 2022. The method used in this study used a total sample, and used a quantitative methodology. The research design used was a cross sectional research design. The sampling technique used is porpossive sampling, with a sample of 88 respondents. The data collection tool is using a questionnaire. Data collection techniques used the square test with the help of SPSS version 28. It was found that from 88 respondents, respondents with mother's knowledge level with good knowledge level category were 38 people (43%), sufficient category was 30 people (34%), and with the category of the mother's lack of knowledge level, as many as 20 people (23%). it was found that bad parenting (permissive and authoritarian) was higher than good, namely 48 (55%), while good parenting (democratic) was only 40 people (45%) From the results of the Chi-Square test, the P value is 0.825 > (0.05). This shows that there is no relationship between mother's knowledge and the incidence of temper tantrums in Jatimakmur Village, Pondok Gede, Bekasi City in 2022. Referring to the research, it is recommended for further researchers to follow up this research with the title Family behavior towards preventing temper tantrums in children aged toddler.